How slack resource affects hospital financial performance: The evidence from public hospitals in Beijing - Chen, Chen; Song, Xinrui; Zhu, Junli (Frontiers in Public Health, 2022)
Background: Beijing is a city with high concentration and congestion of quality medical resources in China. While moderate slack seems to be beneficial to the improvement of medical quality. The actual relationship between hospital slack resources and their performance deserves further exploration. The study aims to analyze the slack resources of public hospitals in Beijing and investigate the relationship between slack and hospital financial performance. Finding a reasonable range of slack to optimize resource allocation. Methods: The panel data of 22 public hospitals in Beijing from 2005 to 2011 were selected as the sample, and the DEA model was applied to measure the main variable using DEAP 2.1. Descriptive statistical analysis was performed using Excel and STATA 15. Pearson correlation coefficient analysis and variance inflation factor test were performed for each variable to avoid multicollinearity. The HAUSMAN test was used to determine the appropriate panel regression model, and then to analyze the influence relationship between the variables. Results: From 2005 to 2011, hospital slack resource transitioned from high to low. The slack measured by the DEA model has an inverted U-shaped relationship with financial performance, with ROA increasing from 4.088 to 8.083 when slack increases from 0 to about 0.378, and then showing a decreasing trend; slack measured by financial indicators has a transposed S-shaped relationship with financial performance, with ROA increasing when slack increase from 3.772 to 5.933. Conclusions: The slack resources of Beijing public hospitals decreased year by year from 2005 to 2011. Moderate slack resources are conducive to the improvement of healthcare quality, but when slack resources increase to a certain level, it will have a negative impact on healthcare quality. Therefore, hospital managers should control the slack within a moderate range according to the hospital operation policy and development plan to obtain the best performance.